2017
DOI: 10.1177/0033294117709260
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Young Children’s Peer Preference by Inhibitory Control and Emotion Regulation

Abstract: This study investigated differences in young children's peer preference by inhibitory control and emotion regulation. In Study 1, 66 preschoolers ( M = 5 years 11 months) were assessed for inhibitory control (IC), emotion regulation (ER), and peer preference. Stroop-like tasks (the black-white task and shine-rain task), the disappointing gift task, and a positive nomination measure were used as measures of IC, ER, and peer preference, respectively. The results of Study 1 showed that participants with high IC o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
0
15
1
1
Order By: Relevance
“…If participants established the link between inhibition and emotional regulation, it would guide them to give better behavioral responses to emotional situations (Denham et al, 2015;Silkenbeumer et al, 2016). It has also been found that participants with better inhibition control ability exhibited better emotional regulation ability compared to lower inhibition control ones (Nakamichi, 2017). And some researchers suggested that participants' inhibition control could predict their emotional regulation and social competence during preschool (Penela et al, 2015).…”
Section: Inhibition Controlmentioning
confidence: 99%
“…If participants established the link between inhibition and emotional regulation, it would guide them to give better behavioral responses to emotional situations (Denham et al, 2015;Silkenbeumer et al, 2016). It has also been found that participants with better inhibition control ability exhibited better emotional regulation ability compared to lower inhibition control ones (Nakamichi, 2017). And some researchers suggested that participants' inhibition control could predict their emotional regulation and social competence during preschool (Penela et al, 2015).…”
Section: Inhibition Controlmentioning
confidence: 99%
“…Low IC is associated with a wide range of outcomes such as obesity, food choices, eating disorders, school performance, peer preferences, externalizing behaviors, aggression, prosocial behaviors, sexual debut, and use of drugs, alcohol, and tobacco [4][5][6][7][8][9][10][11][12]. Low IC may be one of the reasons why youth from low socioeconomic status (SES) and racial and ethnic minority groups engage in more risky behaviors, compared to high SES and majority youth [1,[13][14][15][16]. Thus, studies are needed that investigate the additive effects of race/ethnicity and SES on youth IC as a mechanism of disparities and inequalities in high-risk behaviors [1,10,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The cool-EF battery included four tasks: black-white task (Simpson & Riggs, 2005), shine-rain task (Nakamichi, 2017), 'Simon-says' task (Strommen, 1973), and BDS task.…”
Section: Cool-ef Battery: Timementioning
confidence: 99%